PRODUKSI BIOETANOL DARI BUAH BEBERAPA JENIS MANGROVE DI PAPUA - Wilson P. Aman, Gino N. Cepeda, Mathelda K. Roreng, Susilowati (Jurnal Teknologi Industri Pertanian, 2019)
Mangrove plant has played important role in Papua, both to support the health of ecosystem and the livelihood of its community. As of now, there is only limited knowledge on the utilization of mangroves in Papua. Several varieties in Papua are known to contain carbohydrate and cellulose that can be used to produce food or bioethanol. This study aimed to examine the production of bioethanol using dry grinding and wet grinding methods. The varieties of mangroves used in this research were Rhizophora mucronata Lmk., Rhizophora stylosa Griff., and Bruguiera gymnorrizha. The content of bioethanol as well as the shape and dimension of these varieties were measured in this study. The shape of the mangroves fruit was cylindrical. The mass averages of these mangroves were 180.80 g, 40.39 g and 37.62 g, respectively. The length of the mangrove fruits were 72.33 cm, 41.00 cm and 23.33 cm respectively. The result of the research showed that the best method to produce bioethanol from mangrove fruit was the dry grinding method which resulting in average bioethanol content 6% v/m. Rhizophora stylosa Griff produced the highest bioethanol content, 9.26% v/m, using the dry grinding method and 7.14% with the wet grinding method. Keywords:mangrove fruits, bioethanol, dry grinding,wet grinding